Estimation of average and maximum flows of the Checras river basin through synthetic and rational equations - Herencia Félix, Beatriz Gina (2019)
The main objective of this research is to integrate the morphometric metric parameters of the basin with the statistical information of the National Service of Meteorology and Hydrology SENAMHI, for estimating average flows and maximum flows applying, respectively, the synthetic equations and the rational equations. In the first part the metric parameters of the basin were estimated by applying the principle of georeferencing and superposition of vector and raster layers, using the Arc Gis 10.4 program. Then, by means of the weighted overlapping of thematic maps of the Ministry of Environment MINAM, the runoff coefficient for the Checras river basin is determined. Then, the transformation and statistical treatment of the historical data of SENAMHI related to precipitation records between 1967 and 2008 are carried out, obtaining the intensity of design precipitation and the average precipitation of the basin. With the four main parameters identified: area, runoff coefficient, average rainfall and design rainfall intensity, the series of maximum flows as well as the average and minimum flows of the Checras river are calculated. This allows to characterize the basin in hydrological and climatic terms.